Stowarzyszenie jako element społeczeństwa obywatelskiego - Gulińska, Emilia (Studia Prawa Publicznego, 2023)
This article aims to analyse and assess legal regulations concerning associations as a feature of civil society. In this context, reference is made to the essence of civil society. It should be emphasised that such a society constitutes the foundation of a democratic state under the rule of law. The article presents legal regulations concerning the right to freedom to associate in associations. According to the provisions of the Polish Constitution, the Republic of Poland ensures the freedom of establish and operate trade unions, socio-professional organizations of farmers, associations, citizen movements, and other voluntary unions and foundations, and also guarantees freedom of association to everyone. The article also discusses the notion and attributes of an association, the activities of associations in practice, as well as the problems they face in these areas. The existing legal regulations concerning the establishment and functioning of associations should be assessed positively. However, they are not free of faults. Introducing a less formal process of applying for grants and curbing excessive bureaucracy would be a change for the better in Polish legislation. This would lead to increased cooperation between NGOs and public administration. It needs to be stressed that until non-governmental organisations, including associations, are treated as an equal partner of public administration, we cannot speak about the existence of civil society in Poland.